A cross-sectional study assessing the association between online ratings and clinical quality of care measures for US hospitals: results from an observational study. - Emmert, Martin; Meszmer, Nina; Schlesinger, Mark (BMC Health Services Research, 2018)
BACKGROUND Little is known about the usefulness of online ratings when searching for a hospital. We therefore assess the association between quantitative and qualitative online ratings for US hospitals and clinical quality of care measures. METHODS First, we collected a stratified random sample of 1000 quantitative and qualitative online ratings for hospitals from the website RateMDs. We used an integrated iterative approach to develop a categorization scheme to capture both the topics and sentiment in the narrative comments. Next, we matched the online ratings with hospital-level quality measures published by the Centers for Medicare and Medicaid Services. Regarding nominally scaled measures, we checked for differences in the distribution among the online rating categories. For metrically scaled measures, we applied the Spearman rank coefficient of correlation. RESULTS Thirteen of the twenty-nine quality of care measures were significantly associated with the quantitative online ratings (Spearman p = ±0.143, p < 0.05 for all). Thereof, eight associations indicated better clinical outcomes for better online ratings. Seven of the twenty-nine clinical measures were significantly associated with the sentiment of patient narratives (p = ±0.114, p < 0.05 for all), whereof four associations indicated worse clinical outcomes in more favorable narrative comments. CONCLUSIONS There seems to be some association between quantitative online ratings and clinical performance measures. However, the relatively weak strength and inconsistency of the direction of the association as well as the lack of association with several other clinical measures may not enable the drawing of strong conclusions. Narrative comments also seem to have limited potential to reflect the clinical quality of care in its current form. Thus, online ratings are of limited usefulness in guiding patients towards high-performing hospitals from a clinical point of view. Nevertheless, patients might prefer different aspects of care when choosing a hospita

[A Decade of Online Physician-Rating Websites in Germany: an Assessment of the Current Level of Development]. - Emmert, Martin; Meszmer, Nina (Gesundheitswesen, 2017)
Objective On physician-rating websites (PRW), patients have the opportunity to search for physicians and also evaluate their performance. PRW in Germany has been in existence for a decade; this study aims to provide an overview of the current level of their significance for both patients and the health care system. Methods (1) A systematic internet search was carried out to identify German PRW. (2) Online-derived cross-sectional data (N=1,044 respondents) were analyzed with respect to awareness, usage, and impact of PRW as well as patient preferences when searching online for physicians. (3) An analysis of the structure of online ratings for a random sample of 11% of German dermatologists was conducted. Results In total, we identified 29 PRWs. Slightly more than half of all respondents (54%) were aware of German PRW and every fourth respondent has already used PRW to search for a physician. Approximately 70% of all users stated they had already made a decision for or against a particular physician based on the quality ratings shown on PRW. Almost all dermatologists could be identified on PRW and 93% have already been rated on any PRW (mean number of ratings: 24.55). More than half of all ratings (55%) were positive. Conclusion After one decade of development, PRWs seem to have gained significant importance in the German health care sector. However, high-quality and adequately powered randomized controlled trials are required to determine the impact of PRWs on patient steerag

[Are Facebook Ratings Associated with Hospital Quality and Patient Satisfaction? A Cross-Sectional Analysis of Obstetrics Care in German Hospitals]. - Emmert, Martin; Becker, Sandra; Meszmer, Nina; Sander, Uwe (Gesundheitswesen, 2018)
Social media websites, such as Facebook, have been gaining popularity. Little is known about the usefulness of such online ratings when searching for a hospital. We therefore assessed the association between online Facebook ratings and clinical quality of care measures as well as patient satisfaction for German hospitals in obstetrics care. (1) We identified all German hospitals providing services in obstetrics care based on the German external quality assurance system (2015) and gathered relevant data. (2) Based on a structured dialogue, we determined quality of care results for all hospitals and (3) assigned them to 3 different performance groups. (4) We collected Facebook online ratings as well as (5) patient satisfaction (Patients' Experience Questionnaire, PEQ) results for all included hospitals. (6) We applied the Spearman rank coefficient of correlation. We could find a Facebook page for almost all of the included hospitals (728/752; 96.8%). Facebook hospital ratings in general were mostly positive, especially in obstetrics care. There was no association between Facebook hospital ratings (ρ=0.007; p=0.860) or those for obstetrics care (ρ=0.008; p=0.856) and clinical quality of care measures. In contrast, we could detect an association between Facebook ratings and patient satisfaction scores. The association was stronger for overall hospital ratings (ρ=0.383-0.543; p<0.001) than those for obstetrics care (ρ=0.111-0.250; p<0.05) in particular. So far, Facebook online ratings are of limited usefulness in guiding patients towards high-performing hospitals from a clinical point of view. However, our findings suggest that Facebook ratings may serve as an indicator of patient satisfaction when searching for hospitals. OBJECTIVE METHODS RESULTS CONCLUSION

Arztbewertungsportale: Die Kritik der Ärzte - Emmert, Martin; Sander, Uwe; Kolb, Benjamin; Meszmer, Nina (2017)

Arztbewertungsportale im Internet: Eine aktuelle Bestandsaufnahme - Emmert, Martin; Meszmer, Nina; Schöffski, Oliver (IMPLICONplus, 2014)
Arztbewertungsportale im Internet – Eine aktuelle Bestandsaufnahme von Martin Emmert, Nina Meszmer und Oliver Schöffski Arztbewertungsportale im Internet gewinnen zunehmend an Bedeutung. Ein Grund für die vermehrte Online-Arztsuche liegt in dem Anstieg der Internetnutzung in den letzten zehn Jahren. Der Anteil an Internetnutzern in Deutschland erhöhte sich im Zeitraum von 2003 bis 2013 von 50,1 Prozent auf 76,5 Prozent. Somit zählt das Internet im heutigen Zeitalter zu einer der wichtigsten Informationsquellen für den Bürger. Der hohe Stellenwert des Internets in Kombination mit einem hohen Interesse an Gesundheitsthemen trägt dazu bei, dass Arztbewertungsportale im Internet populärer werden, so beispielsweise für die online Arztsuche. Im Zusammenhang mit der steigenden Nutzung von Arztbewertungsportalen werden immer wieder auch Befürchtungen von Ärzten geäußert, dass insbesondere kritische Patienten Bewertungsportale aufsuchen, was zu einem digitalen Ärztepranger führen könnte. Diesbezüglich erlangte erst kürzlich eine Debatte über die Gewährleistung der Anonymität von Nutzerdaten große Aufmerksamkeit in den Medien. Die Auseinandersetzung wurde ausgelöst durch die Veröffentlichung eines kritischen Kommentars eines Patienten auf dem Portal sanego, der besagte, dass der Patient drei Stunden lang habe warten müssen und der Arzt Patientenakten in Wäschekörben lagere. Auf die Beschwerde des Arztes hin löschte der Portalbetreiber die Beiträge, was den User nicht davon abhielt, die Bewertung erneut mit der gleichen Aussage abzugeben. Daraufhin verlangte der betroffene Arzt Auskunft über die Nutzerdaten von dem Portalbetreiber. Das Bundesverfassungsgericht hat diesbezüglich allerdings entschieden, dass der Portalbetreiber die Namen von anonymen Nutzern nicht an Privatpersonen herausgeben muss und damit den Schutz der Anonymität im Internet gestärkt. Mit dem folgenden Beitrag nehmen wir eine aktuelle Bestandsaufnahme zu den Entwicklungen der Arztbewertungsportale innerhalb der letzten Jahre vor. Hierbei werden die in den letzten Jahren zu dem Thema in wissenschaftlichen Fachzeitschriften publizierten Beiträge aufgegriffen, welche sich beispielsweise mit der Anzahl der Bewertungen, den Bewertungssystemen auf den Portalen, den Inhalten der Freitextkommentare und der thematisierten Sachverhalte der Fragebögen auf den Portalen auseinandergesetzt haben.

Das Nürnberger Krankenhaus-Ranking: Qualitätsinformationen verständlich aufberei-tet - Schöffski, Oliver; Meszmer, Nina; Emmert, Martin (Aktuelle versicherungs- und gesundheitsökonomische Beiträge, 2018)

Do German hospital report cards have the potential to improve the quality of care? - Emmert, Martin; Hessemer, Stefanie; Meszmer, Nina; Sander, Uwe (Health policy (Amsterdam, Netherlands), 2014)
BACKGROUND Hospitals report cards have been put in place within the past few years to increase the amount of publicly reported quality information in Germany. OBJECTIVE The aim of this study was to assess the potential of German hospital report cards to improve quality of care. METHODS First, a systematic Internet search aimed at identifying available report cards was conducted. Second, cross-sectional data (August/September 2013) were analyzed with respect to awareness, comprehension, and impact of report cards by using descriptive analysis and binary multivariate logistic regression models. RESULTS Hospital report cards (N=62) have become broadly available. However, awareness remains low, about one third (35.6%) of all respondents (N=2027) were aware of German hospital report card. Regarding comprehensibility, in 60.7% of all experiments (N=6081), respondents selected the hospital with the lowest risk-adjusted mortality; significant differences could be determined between the report cards (p<.001) with scores ranging from 27.5% to 77.2%. Binary multivariate logistic regression analysis revealed different significant respondent-related predictors on each report card. Finally, an impact on hospital choice making was determined. CONCLUSIONS To increase the potential of hospital report cards, health policy makers should promote the availability of report cards. In addition, the comprehensibility of German hospital report cards cannot be regarded as satisfying and should be enhanced in the future.

Do Health Care Providers Use Online Patient Ratings to Improve the Quality of Care? Results From an Online-Based Cross-Sectional Study. - Emmert, Martin; Meszmer, Nina; Sander, Uwe (Journal of Medical Internet Research, 2016)
BACKGROUND Physician-rating websites have become a popular tool to create more transparency about the quality of health care providers. So far, it remains unknown whether online-based rating websites have the potential to contribute to a better standard of care. OBJECTIVE Our goal was to examine which health care providers use online rating websites and for what purposes, and whether health care providers use online patient ratings to improve patient care. METHODS We conducted an online-based cross-sectional study by surveying 2360 physicians and other health care providers (September 2015). In addition to descriptive statistics, we performed multilevel logistic regression models to ascertain the effects of providers' demographics as well as report card-related variables on the likelihood that providers implement measures to improve patient care. RESULTS Overall, more than half of the responding providers surveyed (54.66%, 1290/2360) used online ratings to derive measures to improve patient care (implemented measures: mean 3.06, SD 2.29). Ophthalmologists (68%, 40/59) and gynecologists (65.4%, 123/188) were most likely to implement any measures. The most widely implemented quality measures were related to communication with patients (28.77%, 679/2360), the appointment scheduling process (23.60%, 557/2360), and office workflow (21.23%, 501/2360). Scaled-survey results had a greater impact on deriving measures than narrative comments. Multilevel logistic regression models revealed medical specialty, the frequency of report card use, and the appraisal of the trustworthiness of scaled-survey ratings to be significantly associated predictors for implementing measures to improve patient care because of online ratings. CONCLUSIONS Our results suggest that online ratings displayed on physician-rating websites have an impact on patient care. Despite the limitations of our study and unintended consequences of physician-rating websites, they still may have the potential to improve patient car

Do online ratings reflect structural differences in healthcare? The example of German physician-rating websites - Meszmer, Nina; Jaegers, Lena; Schöffski, Oliver; Emmert, Martin (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2018)
BACKGROUND Previous surveys have shown that patient satisfaction varies with the regional supply of physicians. Online ratings on physician-rating websites represent a relatively new instrument to display patient satisfaction results. The aim of this study was (1) to assess the current state of online ratings for two medical disciplines (dermatologists and ear, nose and throat (ENT) specialists), and (2) to analyze online derived patient satisfaction results according to the physician density in Germany. METHODS We collected online ratings for 420 dermatologists and 450 ear, nose, and throat (ENT) specialists on twelve German physician-rating websites. We analyzed the online ratings according to the physician density (low, medium, high physician density). For this purpose, we collected secondary data from both physician-rating websites and the regional associations of statutory health insurance physicians. Data analysis was performed using Median tests and Chi-square tests. RESULTS In total, 10,239 online ratings for dermatologists and 8,168 online ratings for ENT specialists were analyzed. Almost all dermatologists (99.3 %) and ENT specialists (98.9 %) were listed on one of the physician-rating websites. A total of 93.5 % of all listed dermatologists and 96.9 % of ENT-specialists were rated on at least one of the physician-rating websites. Significant differences were found in the distribution (i.e., percentage of listed or rated physicians) of the ratings according to the regional physician density on only one physician-rating website (p<0.001). Furthermore, online ratings were shown to be better in regions with a higher physician density on two physician-rating website. On jameda, for example, dermatologist ratings were better in regions with a higher physician density compared to regions with a lower number of physicians (average rating: 2.16 vs. 2.67; p<0.001). CONCLUSIONS Online ratings of dermatologists and ENT specialists hardly differ in terms of regional physician density. Physician-rating websites thus do not appear to be appropriate to mirror differences in the health service delivery structure. Our findings thus do not confirm the results from previously published studie

Eine Trendanalyse von über 190 000 Onlinebewertungen von Orthopäden über die letzten 11 Jahre - Meszmer, Nina (Gesundheitsökonomie und Qualitätsmanagement, 2020)
Objective The objective of this study was to analyze online ratings of orthopaedists over the last 11 years based on the most frequently used physician-rating-website jameda. Furthermore, it should be evaluated if there was an association between the number of ratings and the mean rating. Methods An analysis of all published online ratings of orthopaedists on jameda was conducted from 2008 to 2018.Firstly, descriptive statistics (e.g. number of online ratings) were performed cumulatively and for each year. Secondly, for each year the orthopaedists were divided in 3 groups based on their number of ratings (below-average, average, above average) and it was evaluated if the mean rating significantly differs between these 3 groups (Kruskal-Wallis-test, Mann-Whitney-U-test). Results In sum, the 8126 orthopaedists received 193787 online ratings with a mean rating of 1.97 (SD 1.62). The mean rating of the evaluated orthopaedists has been improving over the last eleven years from 2.38 (SD 1.60) to 2.02 (SD 0.96). The mean number of ratings was 23.85 (SD 32.49). The number of revaluations increased continuously, although the revaluations in 2018 were lower than in the previous year (33,759 vs. 34,367). Orthopaedists with the highest number of ratings often showed a significantly better rating than orthopaedists with a lower number of ratings. For example, in 2018 orthopaedists with the highest number of ratings were significantly better evaluated than orthopaedists with a lower number of ratings (1.90 vs. 2.17 vs. 2.06; p<0.001). Conclusions The active use of the physician-rating-website jameda, based on the number of revaluations and rated orthopaedists, considerably increased over the last years, although the number of revaluations stagnated in 2018. The mean rating of orthopaedists increasingly improved, whereas orthopaedists with the highest number of ratings received better ratings than orthopaedists with a lower number of ratings.
CRIS-Team WoS Importer:2021-01-15

Information presentation features and comprehensibility of hospital report cards: Design analysis and online survey among users - Sander, Uwe; Emmert, Martin; Dickel, Jochen; Meszmer, Nina; Kolb, Benjamin (Journal of Medical Internet Research, 2015)
Keywords: Information presentation; Public reporting; Report cards

[Internet-based Report Cards for Hospital Choice Making in Germany: A Clinical Area-focused Perspective]. - Emmert, Martin; Meszmer, Nina; Simon, Anke; Sander, Uwe (Gesundheitswesen, 2016)
Objectives: Aims of this study are to provide (i) a presentation of quality of care information about German hospitals on internet report cards, and (ii) derive a guidance tool for using certain report cards. Methods: We undertook (i) a systematic internet search to identify hospital report cards, (ii) whereby several inclusion and exclusion criteria were applied, (iii) We developed a scheme to describe the presented quality information, (iv) We also analysed the report cards and (v) evaluated the results and derived further usage guidance. Results: 18 report cards were included. 8 report cards present nationwide quality information while ten report cards focus on regional areas. The AOK Krankenhaus-navigator provides the most information about 5 clinical areas of the external quality assurance (§ 137 SGB V). Regarding the remaining 26 clinical areas, the TK Klinikführer, the Barmer Krankenhausnavi, and the Weisse Liste provide the largest amount of quality information. Qualitätskliniken.de reports on 9, the Klinikführer Rheinland on 8, the Bremer Krankenhausspiegel on 4, and the Hamburger Krankenhausspiegel on 2 additional clinical areas. Conclusions: This study shows that a differentiated view for each clinical area is necessary when searching for information about the quality of hospitals. Further studies should assess the quality of the report cards as well as the information that they displa

Public release of hospital quality data for referral practices in Germany: results from a cluster-randomised controlled trial. - Emmert, Martin; Meszmer, Nina; Jablonski, Lisa; Zinth, Lena; Schöffski, Oliver; Taheri-Zadeh, F (Health Economics Review, 2017)
Objective To evaluate the impact of different dissemination channels on the awareness and usage of hospital performance reports among referring physicians, as well as the usefulness of such reports from the referring physicians’ perspective. Data sources/Study setting Primary data collected from a survey with 277 referring physicians (response rate = 26.2%) in Nuremberg, Germany (03–06/2016). Study design Cluster-randomised controlled trial at the practice level. Physician practices were randomly assigned to one of two conditions: (1) physicians in the control arm could become aware of the performance reports via mass media channels; (2) physicians in the intervention arm also received a printed version of the report via mail. Principal findings Overall, 68% of respondents recalled hospital performance reports and 21% used them for referral decisions. Physicians from the Mass and Special Media group were more likely to be aware of the performance reports (OR 4.16; 95% CI 2.16–8.00, p < .001) but not more likely to be influenced when referring patients into hospitals (OR 1.73; 95% CI 0.72–4.12, p > .05). On a 1 (very good) to 6 (insufficient) scale, the usefulness of the performance reports was rated 3.67 (±1.40). Aggregated presentation formats were rated more helpful than detailed hospital quality information. Conclusion Hospital quality reports have limited impact on referral practices. To increase the latter, concerns raised by referring physicians must be given more weight. Those principally refer to the underlying data, the design of the reports, and the lack of important informatio
Keywords: Public reporting; Hospital quality; Patient referral; Patient counselling; Public health

Public Reporting: Ein Instrument für mehr Qualität im Gesundheitswesen? - Emmert, Martin; Meszmer, Nina (Digitale Gesundheitskommunikation - Zwischen Meinungsbildung und Manipulation, 2018)

Public Reporting zu Krankenhäusern in den USA und in Großbritannien - Emmert, Martin; Meszmer, Nina; Sander, Uwe (Qualitätsmonitor 2017, 2017)

Spotlight Gesundheit – Arztbewertungen - Rischer, Roland; Emmert, Martin; Palmowski, Stefan; Meszmer, Nina (2017)